At a meeting of the freeholders and other inhabitants of the town of Boston : legally assembled at Faneuil-Hall, on Wednesday the 28th of October, 1767 ([Printed by Edes and Gill?], 1767)
Votes and resolutions and the text of a subscription form passed in response to a petition "that some effectual measures might be agreed upon to promote industry, oeconomy, and manufactures; thereby to prevent the unnecessary importation of European commodities, which threaten the country with poverty and ruin." The non-importation agreement was to become effective on December 31, 1767.